Search for lepton flavour violating decays involving tau leptons in the final state at CMS - Luca Guzzi (SciPost Physics Proceedings)
In the Standard Model (SM) lepton flavour numbers are approximately conserved at energies accessible to current experiments, where lepton flavour violation is extremely suppressed. The observation of neutrino oscillations, however, proves that neutrinos are massive particles and allows for additional Lepton Flavour Violating (LFV) processes also at low energies. Nevertheless, these processes are predicted with very low branching ratios and are sensitive to new physics effects, which could manifest as an enhancement in the decay probability. Similarly, Lepton Flavour Universality Violating (LFUV) observables allows for the test of the SM and the study of beyond the SM theories. The latest CMS results from the Higgs, B-physics and exotica groups are presented on the search for LFV and LFUV with tau leptons in the final state. The results are based on data collected in proton-proton collisions at the centre-of-mass energy of 13 TeV.